Influence of Spanish Broom Fibre Treatment, Fibre Length, and Amount and Harvest Year on Reinforced Cement Mortar Quality - Sandra Juradin; Dražan Jozić; Ivanka Netinger Grubeša; Anita Pamuković; Anđela Čović; Frane Mihanović (Buildings, 2023)
The use of natural materials, such as natural fibres, in the construction industry is becoming more frequent. The source of natural fibres should be sought in local plants, such as Spanish Broom in the Mediterranean area. The fibre treatment process was carried out in 8 different ways with alkali 4%, 5%, 6%, 8%, 10% and 15% NaOH solution, and 5% NaOH and 2% Na2SO3 mixture solution and seawater. The fibres were tested for tensile strength. No relationship was established between the concentration of the solution and the tensile strength of the fibres. The influence of the reuse of treatment solution on fibre quality was monitored by X-ray diffraction (XRD), ATR-FTIR, and TG/DTG analysis. Fibres with lengths of 1, 2, and 3 cm were added to cement mortar specimens in amounts of 0.5 and 1 vol%. The flexural and compressive strengths were tested on mortar specimens after 28 days. For fibres 1 and 3 cm long, 0.5% natural fibre content gives higher strength results: about 9% for flexural strength and 13.5% and 11.7% for compressive strength in regard to mortar reinforced with fibres of the same length but with a proportion of 1%. For mortar reinforced with fibre 2 cm long, better results are achieved with 1% fibre content, namely 9% higher flexural strength and 11.2% higher compressive strength compared to mortars with 0.5% fibre content. SEM/EDS analysis showed that the fibres are integrated into the cement matrix but that there is no strong interaction with the binder. For examination and 3D visualisation of mortar specimens, a medical device MSCT (Multi-slice Computed Tomography) was also used. For three consecutive years of Spanish Broom harvesting, an analysis of meteorological conditions and the results of the mechanical strength of reinforced mortars is given. For the examined years, the meteorological conditions did not affect the obtained results. Additional knowledge about the Spanish Broom fibres can introduce this plant to the application of new sustainable building materials.